Global contamination trends of persistent organic chemicals - Loganathan, Bommanna G.; Lam, Paul K. S. (CRC Press, 2012)
"Composed by a diverse group of experts, this reference covers the history, present status, and projected future trends of environmental contamination from highly toxic synthetic chemical pollutants. The text informs practitioners on the effects of man-made chemical pollutants in a comprehensive manner not seen in existing textbooks and references. The book is relevant to professionals and students alike, providing timely coverage on the rising concern towards environmental issues including organic chemicals. Supplementary figures and equations are included for enhanced comprehension of the subject"--